Pandangan Pengurus Mui Kota Binjai Mengenai Peringatan Hari Wafat Ulama (Haul) - Muhammad Rifa'i (Journal Smart Law, 2023)
Haul which in Arabic means year, while for the Indonesian people it has a special meaning, namely : a religious activity to commemorate the death of someone who is represented by the guardians, scholars or kiyai. The commemoration of this haul has been ingrained in this beloved land of Indonesia, I don't know when it started and who started it, what is clear is that this warning has become a tradition that is rooted everywhere, without the slightest doubt in those who do it. Until finally, anti-haul groups emerged. This group attacked so fiercely that finally it raised questions and expressions why the ulama were not the Messenger of Allah, even though the Prophet was the only uswah hasanah, the main role model and guide for all humans? To obtain the answer to this question, this study was directed to literature research and interviews with several Binjai scholars. With the aim of knowing the legal views regarding haul warnings from the scholars, whether it is allowed or not. Therefore, the data that has been collected is analyzed qualitatively, namely the type of data in the form of information, both oral and written, which are not numbers. The data is grouped to make it easier to filter which data is needed or not. After grouping the data, the writer describes it in text form, to make it more understandable, after that the writer draws conclusions from the data so that it can provide answers to the research problem.